Novel biopsy needle and assisted robotic system design for prostate biopsy procedure under MRI - Mahçiçek, Davut İbrahim. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2021., 2021)
Prostate cancer (PCa) is one of the most common cancer type among men. The mortality rate for prostate cancer is signi cantly high compared to other common cancer types which makes it even more concerning for elderly males. For this reason the early and accurate diagnosis of PCa is vital to avoid deaths caused by PCa. In clinical practice, PCa is diagnosed with ultrasound guided biopsy procedure (TRUS-guided biopsy) after observing signs of PCa with di erent pre-screening methods. However, diagnosing PCa with the TRUS-guided prostate biopsy is controversial mainly because US imaging is not able to provide contrast di erence between healthy tissue and le sion. For this reason, biopsy samples are taken statistically from di erent regions of the prostate. On the other hand, magnetic resonance imaging (MRI) can help to dis tinguish lesions from healthy tissues. Therefore, the optimal way to perform prostate biopsy is to perform it under MRI guidance in order to eliminate accuracy concerns. In this thesis, a novel hydraulic needle delivery system that is designed for perform ing MRI-guided prostate biopsy procedure is proposed. The needle delivery system is composed of the main robotic unit, control unit, hydraulic actuator, biopsy gun and biopsy needle. All of these components were designed, manufactured and assembled in the scope of this thesis. The feasibility of the overall system was evaluated through in-vitro phantom experiments under an MRI guidance. The in vitro experiments per formed using a certi ed prostate phantom (incorporating MRI visible lesions). MRI experiments showed that overall hydraulic biopsy needle delivery system has excellent MRI compatibility (SNR Loss < 3%), provides acceptable targeting accuracy (average 2.05 ± 0.46 mm) and procedure time (average 40 minutes).|Keywords : Image Guided Intervention, Minimally Invasive Devices, MRI compatible robotics, Prostate Biopsy, Hydraulic Actuation, Biopsy Needle.
Keywords: Prostate cancer.; Magnetic resonance imaging.; Biopsy.